2022
DOI: 10.7554/elife.74634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cancer on outcome of COVID-19 patients: a systematic review and meta-analysis of studies of unvaccinated patients

Abstract: Background: Since the beginning of the SARS-Cov2 pandemic, cancer patients affected by COVID-19 have been reported to experience poor prognosis; however, a detailed quantification of the effect of cancer on outcome of unvaccinated COVID-19 patients has not been performed. Methods: To carry out a systematic review of the studies comparing the outcome of unvaccinated COVID-19 patients with and without cancer, a search … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…The number of research and participants of the studies included in the meta-meta-analysis is as follows: a total of 58 studies and 709,908 participants were included in the meta-analysis performed by Arayici et al [ 16 ], a total of 81 primary research and 61,532 individuals were included in the meta-analysis performed by Khoury et al [ 17 ], a total of 35 studies and 142,355 participants were included in the meta-analysis performed by Di Felice et al [ 18 ], a total of 57 papers and 63,413 participants were included in the meta-analysis performed by Han et al [ 20 ], a total of 26 studies and 181,323 participants were included in the meta-analysis performed by Venkatesulu et al [ 21 ], a total of 19 studies and 63,019 individuals were included in the meta-analysis performed by Yang et al [ 22 ], a total of 13 papers and 3,775 participants were included in the meta-analysis performed by Salunke et al [ 24 ], a total of 38 primary research and 7,094 participants were included in the meta-analysis performed by Tian et al [ 23 ], a total of 32 research and 46,499 participants were included in the meta-analysis performed by Giannakoulis et al [ 19 ], and a total of 14 papers and 29,900 participants were included in the meta-analysis performed by Parohan et al [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of research and participants of the studies included in the meta-meta-analysis is as follows: a total of 58 studies and 709,908 participants were included in the meta-analysis performed by Arayici et al [ 16 ], a total of 81 primary research and 61,532 individuals were included in the meta-analysis performed by Khoury et al [ 17 ], a total of 35 studies and 142,355 participants were included in the meta-analysis performed by Di Felice et al [ 18 ], a total of 57 papers and 63,413 participants were included in the meta-analysis performed by Han et al [ 20 ], a total of 26 studies and 181,323 participants were included in the meta-analysis performed by Venkatesulu et al [ 21 ], a total of 19 studies and 63,019 individuals were included in the meta-analysis performed by Yang et al [ 22 ], a total of 13 papers and 3,775 participants were included in the meta-analysis performed by Salunke et al [ 24 ], a total of 38 primary research and 7,094 participants were included in the meta-analysis performed by Tian et al [ 23 ], a total of 32 research and 46,499 participants were included in the meta-analysis performed by Giannakoulis et al [ 19 ], and a total of 14 papers and 29,900 participants were included in the meta-analysis performed by Parohan et al [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of five systematic reviews and meta-analyses [ 16 , 18 , 19 , 21 , 24 ] assessed the association between COVID-19 and ICU admission for cancer patients. The pooled ES which was calculated for ICU admission was significantly increased in cancer patients affected by COVID-19 (OR = 1.84, %95 CI: 1.44–2.34, p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent meta-analysis conducted by Di Felice et al, it was found that infected patients with cancer have a twofold higher risk of experiencing a severe form of the COVID-19 illness as well as ICU admission compared to non-cancer patients. The association of SARS-CoV-2 infection with mortality in patients with malignancies was stronger in studies from Asia than from those of North America and Europe ( Di Felice et al, 2022 ). In our region, studies on COVID-19 patients with cancer are scarce and include only a small number of subjects.…”
Section: High-risk Populationmentioning
confidence: 99%
“…A recent meta‐analysis has demonstrated that cancer patients are at more than a 2‐fold increased risk of adverse outcomes of COVID‐19 infections (severe course of the disease, intensive care unit admission and mortality) [ 20 ]. A potential positive impact of vitamin D 3 supplementation on those outcomes could therefore be of particularly high relevance for cancer patients, especially in the light of additional adverse outcomes of the pandemic on cancer care, such as delayed diagnosis and treatment.…”
Section: Vitamin D In Times Of the Covid‐19 Pandemicmentioning
confidence: 99%